Outcome and incidence of postoperative pain at single versus multiple visits of endodontic treatment (Journal of Medical Sciences, 2023)
Aim: To assess the success rate and the incidence of postoperative pain after single- and multi-visit endodontic treatment of teeth with vital and non-vital pulp. Methods: A total of 146 teeth were used in this investigation. The patients were divided into two groups at random and received treatment by two endodontists. Patients in group 1 had their teeth obturated at the same visit, but those in group 2 had their teeth temporarily cemented and obturated after a week. Patients were called back after a week to evaluate their postoperative pain. The criteria of the European Society of Endodontics were used to compare the success rates of the two groups. The Compare means by independent samples, t-test, and descriptive statistics were used to statistically examine the data. The significance level was set at p ˃0.05. Results: The incidence of postoperative pain was (31%) in cases had single visit treatment and (33%) for cases treated under multiple visits, with a slight significant difference (p= 0.054). Teeth with vital pulp experienced more postoperative pain (45%) than teeth with non-vital pulp (19%), with statistically significant difference (p=0.035), in both treatment regimen. The success rate was higher in both groups, single visit treatment (88%) and multiple visit treatment (90%) at (p=0.043). Conclusion: Within the limitations of the current study, there was a high incidence of postoperative pain after root canal treatment. No significant difference be present in postoperative pain after single-visit or multiple-visit treatment. In addition, neither single-visit nor multiple-visit has great effect over the other in terms of the success rate.